Surgical Removal of a Migrated WATCHMAN Device - Andrew G. Saleeb; Juan M. Farina; Asher Jenkins; Rawan Zeineddine; Kenan Shawwaf; Eric H. Yang; Said Alsidawi; Dawn E. Jaroszewski; Francis X. Downey (Methodist DeBakey Cardiovascular Journal)
The WATCHMAN™ atrial appendage closure device is designed to reduce the risk of stroke in patients with nonvalvular atrial fibrillation who are not suitable candidates for long-term oral anticoagulation therapy. However, the device also carries small risks, including procedural complications such as device migration, embolization, or pericardial effusion. We describe a case of WATCHMAN device migration requiring surgical retrieval.